Coastal nutrient enrichments facilitated reproductive output in exotic mangrove species over two decades - Huang, Zijian; Li, Zhen; Wang, Minhuang; Zhu, Dehuang; Yang, Qiong; Yu, Shixiao (Frontiers in Forests and Global Change, 2023)
Litterfall may facilitate the outperformance of exotic species by inducing better resource acquisition and reproductive performance. However, the drivers that determine litterfall patterns in exotic and native species have remained insufficiently investigated due to the lack of long-term observations. Here, we employed empirical dynamic modeling on a two-decade-long litterfall observation (1999–2019) in a subtropical mangrove forest in Shenzhen, China, to evaluate the relative importance of environmental drivers on different species. We found that mangrove leaf litterfall in both exotic and native species was strongly altered by temperature, and the causal relationship was stronger in the dominant exotic species Sonneratia apetala compared to native species. However, the main driver of reproductive output differed largely between exotic and native species; temperature was the main cause of native reproduction, whereas coastal nutrients drove the reproductive output of exotic species. Our study highlighted that high nutrient availability in Shenzhen Bay in the past decade allowed the exotic species S. apetala to gain better reproductive output than native species. We imply that enriched nutrients in coastal water likely contributed to exotic dominance in China’s coastal mangrove forest.